Profil Hasil Pemeriksaan Crossmatching Incompatible pada Pasien dengan Metode Gel Test - Eni Ruwiyanti (Poltekkes Kemenkes Semarang, 2020)
Laboratory examiners before giving blood transfusions (PretransfusionTesting) is a vital part of the transfusion activity. Incompatible Crossmatching blood tests on patients is consistent if we had to crossmatching one or more of the one or all of the positive so that blood is stated compatible with the patient. The gel test method has many advantages compared to the tubulating method other than the halting factor time. The gel test procedures have also been simpler, more practical, and easier results reading done. The goal of this study to identify the output of crossmatching receipts on the geltest method of 2019 in Indonesian Redcross of Klaten, this research method using a descriptive design with a sectional cross approach. And data retrieval using secondary data. The results shows the number of inconsistencies in patients of 116 cases. As many as 57% (66) incompatible crossmatching major minor and autocontrol of 43%(50) found a type of compatible major. The conclution are that in Indonesian Redcross of Klaten found most frequently in the diagnosis of anemia 59% (69) patients. The result of incompatible minor and positive autocontrol 57% more than compatible major 43%. Incompatible crossmatching receipts per month in the high Indonesian Redcross of Klaten is in April of 27 patients or 23%.